2021
DOI: 10.18203/2349-3291.ijcp20210104
|View full text |Cite
|
Sign up to set email alerts
|

Survival rate and length of stay of preterm babies less than 1500 grams in a neonatal unit in Port Harcourt, Nigeria

Abstract: Background: The survival rate and length of stay of preterm babies which is usually of concern to both parents and clinicians is critical in counselling parents at the time of admission and also assesses the efficiency of the neonatal unit thus necessitating the present study.Methods: A prospective study carried out over 30 months in the neonatal unit of Rivers State University Teaching Hospital, Nigeria.Results: Of 115 preterm babies <1500 gm studied, commonest gestational age and birth weight were 30 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…The present research study is also consistent with studies by Wang et al (2017) and Rojsanga (2018) which reported that birth weight positively affected an infant's survival. Previous studies indicated that survival of infants was very low in infants less than 1000 grams (Vilanova et al, 2019;West, 2021). The findings of the present study found that the majority of the survival group (47.5%) had birth weight at 1,000-1,499 grams whereas those of the non-survival group (76.2%) had birth weight less than 1,000 grams (Table 2).…”
Section: Discussionsupporting
confidence: 51%
“…The present research study is also consistent with studies by Wang et al (2017) and Rojsanga (2018) which reported that birth weight positively affected an infant's survival. Previous studies indicated that survival of infants was very low in infants less than 1000 grams (Vilanova et al, 2019;West, 2021). The findings of the present study found that the majority of the survival group (47.5%) had birth weight at 1,000-1,499 grams whereas those of the non-survival group (76.2%) had birth weight less than 1,000 grams (Table 2).…”
Section: Discussionsupporting
confidence: 51%